Preparation of Sponge Cake from Banana flour as Substitution for Wheat Flour with Soybean Flour Enrichment - Donald S Napitupulu; Terip Karo-Karo; Zulkifli Lubis (Universitas Sumatera Utara, 2013)
This research was conducted to find the effect of the addition banana flour and soybean flour on the quality and characteristics of sponge cake. This research was performed in November 2011 - April 2012 at the Laboratory of Post-Harvest, Research Institute of Agricultural Technology, North Sumatra, using factorial completely randomized design with 2 factors, namely banana flour concentration (P): 15%, 30%, 45%, and 60% and soybean flour concentration (K): 0, 5%, 10%, and 15%. Parameters analyzed were moisture content, protein content, ash content, degree of swelling, organoleptic values of flavor, taste, and texture. The results showed that banana flour concentration gave highly significant effect on moisture content, degree of swelling, and organoleptic values of taste, and gave no significant effect on protein content, ash content, organoleptic values of flavor and texture. Soybean flour concentration gave highly significant effect on moisture content, ash content, degree of swelling, organoleptic values of taste and texture, and gave no significant effect on protein content, and organoleptic values of flavor. The combination of banana flour concentration and soybean flour concentration gave no significant effect on all parameters. The combination of banana flour concentration of 30% and soybean flour concentration of 5% gave the good and acceptable quality of sponge cake. Key words : Wheat Flour, Banana Flour, Sponge Cake, Soybean Flour